Efficacy of Autologous Serum with Antihistamine Therapy in the Treatment of Chronic Urticaria - Naz, Syeda Sibgha; Mushtaq, Shegref; Akhtar, Aisha; Ahmed, Najia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the efficacy of autologous serum with Antihistamine therapy in treating chronic urticaria. Study Design: Quasi-experimental study. Place and Duration of Study: Dermatology Department, Pak Emirate Military Hospital, Rawalpindi Pakistan, from Jul 2018 to Jan 2019. Methodology: One hundred four patients of chronic urticaria (≥3 times/ week for ≥6 weeks) with ages ranging from 16 to 70 years were assigned the treatment groups using a lottery method. i.e., Group-A (autologous serum therapy) and Group-B(Antihistamine therapy). During the eight weeks of therapy, weekly Urticaria Activity Scoring (UAS-7) was utilized to quantify response in terms of the number of weals and pruritus. Results: Of 104 patients, 75(72.12%) were females, and 29(27.88%) were males. Sixty-nine patients were between 18 to 35 years of age, with a mean age of 37.79±10.15 years in Group-A and 38.04±10.98 years in Group-B. Efficacy of Group-A (autologous serum therapy) was seen in 40(76.92%) patients while in Group-B (Antihistamine therapy) it was seen in 25(48.08%) patients(p-value =0.002). Conclusion: Autologous serum therapy is more effective than Antihistamine therapy in treating chronic urticaria.